Solving Sprawl: - Benfield, F. Kaid (Natural Resources Defense Council, 2001)
The best hope for addressing the problem of sprawl is "smart growth" - an approach to development that is town-centered and transit- and pedestrian-oriented, and which mixes residential, commercial, and retail development. It also preserves open space and other environmental amenities. Solving Sprawl shines a spotlight on American communities that are applying smart growth principles in successfully addressing the problem of sprawl. It offers examples that illustrate key concepts and tells the story of how this new approach to development has caught hold across America. It reports the good news that successful smart-growth developments can now be found throughout the country. The book details 35 diverse smart-growth stories and celebrates those who are leading the way in solving sprawl. Each chapter showcases a wide variety of solutions with projects of all sizes in urban, suburban, and exurban settings. Projects profiled include Adidas Village in Portland, Oregon; the MCI Center in Washington, D.C.; Quality Hill in Kansas City, Kansas; Suisun City redevelopment in Suisun City, California; growth control initiatives in Boulder, Colorado; Pearl Lake in Almira Township, Michigan; and more. Interspersed throughout are sidebars that offer additional examples and reminders of the sprawl-related environmental and social problems that smart growth helps overcome. The book also includes a glossary of planning terms and land-use concepts